Prevalence of hepatitis B vaccination and serological immunity of women in prenatal care at an university outpatient clinic in Southern Brazil - Silva, Carolina Silveira da; Glitz, Alisson; Micheletti, Gabriela Dezoti; Silva, José Matheus da; Bisol, Vitória Martins; Silveira, Mariangela Freitas (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Viral Hepatitis B is an infection with a high transferability, and delivery is the main form of transmission to newborns. Investigating HBV infection in pregnant women should be undertaken through research on the surface antigen of Hepatitis B virus (HBsAg), and the immunity to the virus should be assessed by the presence of the antibody against the surface antigen of the Hepatitis B virus (anti-HBs). Vaccination is recommended during pregnancy to all patients with non-reactive HBsAg and anti-HBs results. Objective: To analyze data related to the preventive measures of HBV infection in pregnant women who underwent prenatal follow-up at the Gynecology and Obstetrics outpatient clinic of the Medical School of Universidade Federal de Pelotas (Rio Grande do Sul State). Methods: A cross-sectional study was carried out by analyzing the medical records of patients from the Obstetrics and Gynecology outpatient clinic. Data related to the preventive measures of HBV infection, the socioeconomic profile and ethnicity of these patients were analyzed and described. Results: The total number of pregnant women studied was 121, aged between 15 and 46 years old, mostly white, who had a partner, and earned more than two minimum wages. Seventy-one patients presented non-reactive HBsAg, and no patient showed a reactive test. Roughly 40% of pregnant women had not undertaken the HBsAg test. Among the 121 analyzed pregnant women, 74 (61%) performed the anti-HBs test, and only 14 (19%) showed they were reactive. Approximately 15% showed complete vaccination before prenatal care, but only 9 of them had taken the reactive anti-HBs test. Conclusion: A lower expected number of pregnant women who underwent screening for infection (HBsAg), and immunity (anti-HBs) from Hepatitis B, and there was a strong incomplete adhesion to vaccination. It is necessary to encourage the request and performance of the tests and adequate medical records filling out, as well as confirmation on the adhesion to the three doses of the vaccination schedule recommended by the Brazilian Ministry of Health.